PENINGKATAN MOTIVASI BELAJAR SISWA BERBANTUAN MEDIA PADLET PEMBELAJARAN IPAS KELAS V SD PLUS IGM PALEMBANG - Zalis, Bella Sonianica; Anwar, Yenny; Maryanti, Atika Dwi (UNIB Press, 2025)
This classroom action research aimed to enhance student learning motivation in IPAS subject (Science and Social Studies) throught the strategic use of the interactive digital media, padlet. The study was motivated by the low initial engagement and lack of active participation observed among fifth-gradestudents at SD Plus IGM Palembang. The research involved 24 students and was conducted in two cycles following the kurt lewin model. Data were collected using a likert-scale questionnaire based on six motivation indicators from Hamzah B. Uno. In pre-cycle observation, the average motivation score was low at only 49.12%. following the initial intervention in cycle I, which integrated padlet with the Problem-Based Learning model, the motivation score increased to 61.72%. Subsequently, in cycle II, the learning strategy was refined by optimizing padlet use- including varied activities like uploading images and videos, and refining group composition which resulted in a final score of 81.72%. The consistent improvement, with an overall incrase of 32.60% from the pre-cycle to cycle II , indicates that padlet is effective in fostering a more interactive and collaborative learning environment. Padlet successfully encouraged active student participation, boosted confidence in expressing opinions, and increased enthusiasm for completing tasks. This indicates that padlet is effective in enchancing students learning motivation.